The mystery on Blizzard Mountain - Warner, Gertrude Chandler, 1890-1979.; Soileau, Hodges (Morton Grove, IL : A. Whitman, 2002)
When the Alden children go camping on Blizzard Mountain, a place said to be inhabited by a ghost looking for buried treasure, they begin to think someone or something is trying to scare them off.
460
Accelerated Reader AR
Keywords: Ghosts -- Fiction; Buried treasure -- Fiction; Mountains -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories